A Chance to Learn : Knowledge and Finance for Education in Sub-Saharan Africa - World Bank (Washington, DC, 2013)
Without rapid and substantial improvements in education access and quality, broader poverty reduction efforts in Sub-Saharan Africa will be thwarted. This report argues that at the cusp of the 21st century, the opportunity to address the often intractable problems of education in Sub-Saharan Africa is perhaps greater than at any time in the past two decades. Economic growth has resumed in many countries; the political commitment to education development is strong; and new democracies have created a more favorable environment for the participation of civil society and communities in policy formulation and program implementation. Also, information and communication technology offer new opportunities to overcome the constraints of distance and time. Finally, increased debt relief and stronger international partnerships in favor of education will help ease the financing constraints on accelerating education development. The report proposes a strategy and a program of action for the World Bank's Africa Region, which is striving to support countries in their efforts to accelerate education development. It summarizes the challenges facing education development in Africa, suggests key elements of country responses, discusses the implications of these responses, and proposes actions for improving the Bank's effectiveness as a partner in education development. In doing so, it lays the groundwork for future increases of World Bank support for education development in Africa.